2017
DOI: 10.3846/16111699.2017.1357655
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Financial Management Performance of the Spanish Aerospace Manufacturing Value Chain

Abstract: We study financial management performance during 2008–2013 for the Spanish aerospace manufacturing value chain and the links with managerial decisions. Data from company financial statements is analysed with Principal Component Analysis, Data Envelopment Analysis and an Artificial Neural Network. Top financial performers focus on liquidity management rather than on returns: both in the short term, by increasing levels of current assets and funding them with short-term liabilities, as well as increasing asset t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…A few studies evaluating the performance of aerospace and defence industry employed single dimensional measures (Herranz, Estévez, Oliva, & Dé, 2017;Martin, White, & Hartley, 1996). However, multidimensional performance models provide a more comprehensive measure by considering the relevant input and output factors into account.…”
Section: Dynamic Slack-based Measurementioning
confidence: 99%
“…A few studies evaluating the performance of aerospace and defence industry employed single dimensional measures (Herranz, Estévez, Oliva, & Dé, 2017;Martin, White, & Hartley, 1996). However, multidimensional performance models provide a more comprehensive measure by considering the relevant input and output factors into account.…”
Section: Dynamic Slack-based Measurementioning
confidence: 99%
“…The global market is the industry's biggest market. The aircraft industry is a strategic industrial sector to boost other industrial ecosystems, significant potential growth, and global market orientation (Herranz, Estévez, and Oliva 2017).…”
Section: Results Indonesian Aerospace (Iae) Marketsmentioning
confidence: 99%
“…Specifically, the authors identified those bus lines which were performing well, those to be supported and subsidised and those to be expanded due to the high level of potential demand. Benchmarking yields information and enables agility and accuracy in the strategy setting process (Herranz et al, 2017).…”
Section: Efficiency Analysis In Retailingmentioning
confidence: 99%